L’arco dell’identità e Paul Ricœur - Canullo, Carla (B@belonline, 2021)
Just as Ricœur spoke of a “hermeneutic arch” for interpretation – which holds together the terms that Dilthey had separated, namely explaining and understanding - in the same way one can read the arch of identity that the French philosopher has traced since Le volontaire et l’involontaire, introducing for the first time the expression of cogito brisé, broken cogito. Starting from this concept, Ricœur traced the arc of identity, the complexity of which he progressively showed, up to the famous formulation of narrative identity, in which the heart of a subject is synthesised, which is not a self-position but (a) living “who” of which narrative identity plays the temporal dimension. Another form, which is not Ricœurian, is the oikological identity, i.e. the identity of one who “is” and discovers himself by dwelling "in front of" - in front of a You, in front of the world, religion, culture or in front of another "who". In this way, the arc of identity is enriched: from a single tension into a series of arcs which, together, develop the arc that relaunches identity towards the new forms that experience may assign to it.